The Service Encounter: Diagnosing Favorable and Unfavorable Incidents - Bitner, Mary Jo; Booms, Bernard H.; Tetreault, Mary Stanfield (Journal of Marketing, 1990)
The service encounter frequently is the service from the customer's point of view. Using the critical incident method, the authors collected 700 incidents from customers of airlines, hotels, and restaurants. The incidents were categorized to isolate the particular events and related behaviors of contact employees that cause customers to distinguish very satisfactory service encounters from very dissatisfactory ones. Key implications for managers and researchers are highlighted.